ANALYSIS OF THE HIGH-TEST CAST IRON QUALITY WITH APPLICATION OF METHODS OF MATHEMATICAL STATISTIC - V. A. Chajkin; V. V. Ishutin; N. V. Chajkina; V. P. Meshcheijakov; I. S. Shchemelev (Литьë и металлургия, 2006)
is determined that application of bowl with lid for spheroidizing processing of melt allows to receive high-test cast iron without pyroeffect and smoke emission.